International Marketing Track Best Paper Award at the Academy of Marketing Conference, Hull, U.K - Christodoulides, Paul (My University, 2026)
International Marketing Track Best Paper Award at the Academy of Marketing Conference, Hull, U.K. for “Emotional intelligence as a facilitator of long-term orientation in exporter-importer relationships” (with L. Leonidou, B. Aykol, T. Fotiadis) (Cook 2017)
Keywords: Sciences